2017
DOI: 10.31234/osf.io/vu8je
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robustness of the adult statistical word segmentation literature: Part 1

Abstract: We report the first set of results in a multi-year project to replicate every adult statistical word segmentation study. We reported replications of six experiments. The purpose of these replications is both to assess the strength of the findings in the statistical learning literature but also to provide more accurate effect size estimates. In every instance, we were able to replicate successful learning. However, many theoretically important modulations of that learning failedto replicate. Moreover, learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…However, it is widely observed that effects in the literature tend to be inflated (Open Science Collaboration, 2015;Trikalinos et al, 2004). Moreover, there is some evidence that statistical word segmentation effects are smaller in the general population than in college students (the population used by Bonatti and colleagues) (Hartshorne et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is widely observed that effects in the literature tend to be inflated (Open Science Collaboration, 2015;Trikalinos et al, 2004). Moreover, there is some evidence that statistical word segmentation effects are smaller in the general population than in college students (the population used by Bonatti and colleagues) (Hartshorne et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we describe the methods and results for an online replication of experiment 2A from a classic statistical wordsegmentation paper by Newport and Aslin (2004) (henceforth: NA04). This experiment is part of a larger project to systematically replicate as many experiments involving statistical word learning in adults as possible and follows the first part of replications completed in 2017 (Hartshorne et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This experiment is part of a larger project to systematically replicate as many experiments involving statistical word learning in adults as possible and follows the first part of replications completed in 2017 (Hartshorne et al, 2017).…”
Section: Introductionmentioning
confidence: 99%